2012
DOI: 10.1177/0193723512467193
|View full text |Cite
|
Sign up to set email alerts
|

Sports-Based Interventions and the Local Governance of Youth Crime and Antisocial Behavior

Abstract: Drawing on analysis of youth crime and antisocial behavior reduction policies and a qualitative study of sports-based interventions (SBIs) in England, the article considers three ways in which SBI staff, managers, partners, and participants suggest projects contribute to youth crime reduction: encouraging young people's "selftransformation" through the development of supportive and mentoring relationships (changing people), providing alternative activities and "sanctioned" spaces (changing environments), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 48 publications
(93 reference statements)
1
57
0
1
Order By: Relevance
“…This ability to successfully apply for funds might be a result of the involvement of Rotterdam Sportsupport. Kelly (2013), for instance, found that involving strategic partners (e.g., Rotterdam Sportsupport) may increase possibilities to acquire local funding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ability to successfully apply for funds might be a result of the involvement of Rotterdam Sportsupport. Kelly (2013), for instance, found that involving strategic partners (e.g., Rotterdam Sportsupport) may increase possibilities to acquire local funding.…”
Section: Discussionmentioning
confidence: 99%
“…Rütten, Abu-Omar, Frahsa, and Morgan (2009) and Hartog, Wagemakers, Vaandrager, Dijk, and Koelen (2013) for instance, found that intersectoral action is also required to increase the physical activity of other socially vulnerable groups such as immigrant women and primary care clients. Kelly (2013) found that partnerships of practitioners (e.g., youth workers and volunteers at local sports clubs) are important because they can lead to shared resources and referral pathways. If strategic partners and community members are also included in such partnerships, access to funding increases, opportunities to influence policymaking grow, and possibilities to publish the results of the partnership arise (Kelly, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this mode, Baltimore's PAL program demonstrates one example of sports-based interventions that are designed to change individual behaviors, urban spaces, and social interactions between communities and policing organizations (Kelly, 2013), particularly in regard to "hard to reach" (Crabbe, 2007) populations within cities. Further, the PALs were also a "microcosm of American liberal social policy" (Hartmann, 2016, p. 73), since their very development, and ultimate demise, was inextricably linked to the shifting conditions and dynamics of neoliberal urban governance.…”
Section: Introductionmentioning
confidence: 99%
“…Such criticism is presented in the first two articles; it is displayed that sport practices cannot change social structures or reduce the poverty and unemployment that arguably create social problems (e.g Coakley 2002Coakley , 2011aCollins & Kay 2014;Kelly 2011Kelly , 2012Pitter & Andrews 1997), that sport associations are primarily interested in sport for competition and not social work (Coalter 2007b), that sport practices contribute to selection and stratification (Hartmann & Kwauk 2011) and that skills and competences attained in a sport setting are rarely transferable to other social settings (Wagnsson 2009). In addition, sport has even been described in research as a generator of social problems (Anderson 2010;Eitzen 2012).…”
Section: Critical Perspectives In Researchmentioning
confidence: 99%